PERENCANAAN PAJAK DAN ENVIRONMENTAL SOCIAL GOVERNANCE TERHADAP MANAJEMEN LABA DENGAN PROFITABILITAS SEBAGAI PEMODERASI - Atiqah, Atiqah; Saputro, Sadham Nur Hidayah (Department of Accounting-Faculty of Economic and Business (FEB), 2024)
This research aims to examine the influence of tax planning, environmental, social, and governance (ESG), on earnings management with profitability as moderation. This is quantitative research using secondary data from financial statements and sustainability reports. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The sample is selected using purposive sampling method, resulting in 65 data as samples. This study uses multiple linear regression analysis as a hypothesis test using IBM SPSS 29.The results of this research indicate that tax planning has not significant effect on earnings management. Conversely, environmental, social, and governance (ESG) and profitability has a negative and significant effect on earnings management. The results of this research show that profitability can moderate the effect of tax planning on earnings management but profitability can not moderate the effect of environmental, social and governance on earnings management.